VALIDITY OF 3D PAGEFLIP POCKET BOOK CONTAINING POACEAE SPECIES IN GALAM VEGETATED SWAMP, BATI-BATI DISTRICT - Vika Wulansari Pohan; Dharmono Dharmono; Maulana Khalid Riefani (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Species of Poaceae may be used as mastering objects, based on local potential, as learning resources, thats in accordance with technological developments, making it into 3D pageflip based pocket book. A valid pocket book, as learning resources, can be defined if it has been validated by experts in field. Validation role to assess the prototype, and eligible for more developmental phases. The aim of this research is to determine the validity of the pocket book, which contains material about Poaceae species in galam vegetated swamps. This pocket book is in the form of a 3D pageflip. This development uses Tessmer's formative evaluation model. The value of validity is determined by 2 experts. The results of the study confirm that the product that has been developed is very valid, especially for expert consequences of 93.42%.